A comparative visual framework of Prophet Adam’s narratives: The Quran, Tafsir Nur al-Ihsan, and the Bible. - Arom, Nurul Hidayah; Badi, Jamal Ahmed Bashier; Nik Abdullah, Nik Md. Saiful Azizi (Research and Scientific Innovation Society (RSIS International), 2025)
This project introduces an innovative visual pedagogical framework entitled “Prophet Adam Across Religious Texts,” which transforms dense qualitative comparisons of the Qur’an, Malay exegesis Tafsir Nur al-Ihsan, and the Bible into interactive infographic modules. The core innovation lies in reimagining a research project conducted under the ISTAC-IIUM Research Grant, “Isra’iliyyat in the Adamic Narrative: A Comparative Analysis of the Bible and Tafsir Nur al-Ihsan.” By integrating multilingual sources (the Arabic Qur’an, Malay tafsir, and English Bible) side by side, the framework enhances accessibility, fosters critical comparative thinking, and equips educators with a low-cost, digitally friendly tool for teaching Islamic studies and comparative religion. The project also highlights how Tafsir Nur al-Ihsan integrates Isra’iliyyat narratives. Key features of the framework include infographics on four central themes: (1) creation of Prophet Adam and Hawa, (2) God’s command and the Forbidden Tree, (3) temptation and wrongdoing, and (4) consequences. The design can potentially be adapted for teaching slides or interactive digital formats in both classroom and online platforms, subject to pilot testing and user feedback. The anticipated outcomes include making complex theological discourse more accessible, stimulating critical thinking, fostering comparative insights between Isra’iliyyat, the Qur’an, and the Bible, and enhancing student engagement through visual learning. Ultimately, this project demonstrates how qualitative, library-based research can be innovatively re-envisioned as a practical pedagogical design for diverse educational contexts.